Metabolome integrated with transcriptome reveals the mechanism of three different color formations in Taxus mairei arils - Yan, Yadan; Wen, Yafeng; Wang, Ye; Wu, Xingtong; Li, Xinyu; Wang, Chuncheng; Zhao, Yanghui (Frontiers in Plant Science, 2024)
Maire yew (Taxus mairei), an evergreen conifer, has high ornamental and medicinal value. The arils of this species has three different colors. However, the variation mechanisms of arils color formation remains unclear. Here, the gene expression and metabolite concentration were profiled for red (RTM), yellow (YTM), and purple (PTM) arils in different developmental stages. A total of 266 flavonoids and 35 carotenoids were identified. The predominant pigments identified in YTM were epiafzelechin, lutein, and β-Cryptoxanthin, while malvidin-3,5-di-O-glucoside and apigenin played crucial roles in PTM. And significant differential expression was observed among the HCT, DFR, LAR, ANS, crtB, NCED, and CCoAOMT genes across different color arils. During the maturation of yellow arils, the upregulation of HCT was strongly correlated with the accumulation of epiafzelechin. The diminished expression of DFR, LAR, and ANS seemed to inhibit the production of delphinidin-3-O-rutinoside. The decrease in crtB expression and concurrent increase in NCED expression potentially regulate the heightened accumulation of lutein. Meanwhile, the accumulation of β-cryptoxanthin appeared seemed to be positively influenced by NCED. As aril turning purple, the decreased expression of CCoAOMT seemed to facilitate the synthesis of apigenin. The substantial upregulation of DFR promoted the production of malvidin-3,5-di-O-glucoside. Additionally, the overexpression of MYBs may plays the important role in regulating the formation of different colored arils. In total, 14 genes were selected for qRT-PCR validation, the results indicated the reliability of the transcriptome sequences data. Our findings could provide valuable insight into the molecular breeding, development, and application of Maire yew resources.